Analisa Usability Desain Aplikasi Controlling Calories untuk Mendapatkan Berat Badan Ideal - Fernando Trisno Swandi; Restyandito; Kristian Adi Nugraha (Lentera Dua Indonesia, 2023)
Having an ideal body weight is a wish and dream for everyone. The ideal body weight is the body shape desired by every group, both women and men, both at old and young ages. Unhealthy eating patterns and consumption of foods that are difficult to digest will make the body overweight, due to excessive accumulation of calories. Being overweight (obese) should not be ignored, because it can have a negative impact on the health of the body. The design of a calorie control application design can help users find out the number of calories needed for the body. The user centered design method is used as a reference in creating application interfaces that suit user needs, so that users can interact quickly and easily to use this application interface. In this study, usability testing was carried out by paying attention to 3 aspects, namely effectiveness, efficiency, and satisfaction according to ISO-9241-11 standards, which resulted in an effectiveness value of 97.65%, 68% efficiency, and 86.57% satisfaction. After obtaining the values of these 3 aspects, a simplification is carried out using the single usability metric method, which produces a value of 84,07%. So it can be concluded that the purpose of the application being tested has been fulfilled.